2012
DOI: 10.1017/s0954579412000181
|View full text |Cite
|
Sign up to set email alerts
|

In search of security: The latent structure of the Adult Attachment Interview revisited

Abstract: Building on Roisman, Fraley, and Belsky, who produced evidence for two modestly correlated dimensions (i.e., dismissing and preoccupied states of mind) underlying individual differences in attachment as assessed by the Adult Attachment Interview using the Main and Goldwyn classification system, this report replicates and extends relevant evidence in a large sample of adults (N = 842) who completed the Adult Attachment Interview coded using Kobak's Adult Attachment Interview Q-Sort. Principal components analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
58
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 42 publications
10
58
0
1
Order By: Relevance
“…The cards are sorted into a forced normal distribution ranging from least characteristic to most characteristic of the transcript and these distributions are then correlated with prototype sorts. As already noted, Haydon et al (2012) demonstrated with the UIUC sample used in the current report that adults’ AAI narratives vary with respect to two weakly correlated state-of-mind dimensions: dismissing states of mind (e.g., “adjectives supported by vague or shallow memories versus adjectives supported by detailed episodic memories”) and preoccupied states of mind (“is confused or overwhelmed with information about parents versus information about parents is adequate and well organized”). As such, this analysis used the same operationalization of the state-of-mind dimensions as reported in Haltigan et al (2014) with respect to the SECCYD sample and in Haydon et al (2012) with respect to the UIUC sample, both of which leveraged the dismissing and preoccupied prototype scores of the Q-sort (see Spangler & Zimmermann, 1999).…”
Section: Methodssupporting
confidence: 68%
“…The cards are sorted into a forced normal distribution ranging from least characteristic to most characteristic of the transcript and these distributions are then correlated with prototype sorts. As already noted, Haydon et al (2012) demonstrated with the UIUC sample used in the current report that adults’ AAI narratives vary with respect to two weakly correlated state-of-mind dimensions: dismissing states of mind (e.g., “adjectives supported by vague or shallow memories versus adjectives supported by detailed episodic memories”) and preoccupied states of mind (“is confused or overwhelmed with information about parents versus information about parents is adequate and well organized”). As such, this analysis used the same operationalization of the state-of-mind dimensions as reported in Haltigan et al (2014) with respect to the SECCYD sample and in Haydon et al (2012) with respect to the UIUC sample, both of which leveraged the dismissing and preoccupied prototype scores of the Q-sort (see Spangler & Zimmermann, 1999).…”
Section: Methodssupporting
confidence: 68%
“…Allen and colleagues (Allen, 2008; Allen & Manning, 2007; Allen & Miga, 2010) argue that by adolescence, attachment states of mind in part represent individuals’ growing capacity for emotion regulation within the social domain. As previously discussed, researchers have found evidence that preoccupied states of mind in particular are associated with dysregulated emotional experiences (e.g., Bernier et al, 2004; Fortuna et al, 2011; Haydon, Roisman, & Burt, 2012; Haydon et al, 2011; Larose & Bernier, 2001; Roisman et al, 2004; Tarabulsy et al, 2012). Indeed, preoccupied states of mind regarding early caregiving experiences imply continued rumination on these experiences and associated emotional distress.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, preoccupied states of mind have been associated with emotional dysregulation or heightening of affect. Specifically, preoccupied states of mind have been linked with more self-reported distress (Bernier et al, 2004; Larose & Bernier, 2001; Larose et al, 2005; Roisman et al, 2004; Tarabulsy et al, 2012), expressing more negative affect during conflict discussions with relational others (Fortuna et al, 2011; Haydon, Roisman, & Burt, 2012), identifying with more negative self-views (Haydon et al, 2011), and with dysregulated emotional experiences during the AAI (Roisman et al, 2004). Additional researchers suggest that individuals with preoccupied states of mind tend to use detrimental emotion regulation strategies involving elevated emotional needs and reactions, as well as rumination upon emotionally distressing experiences (Cole-Detke & Kobak, 1996; Kobak et al, 1993; Kobak & Sceery, 1988).…”
Section: Preoccupied States Of Mind Regarding Attachment and Nssimentioning
confidence: 99%
“…One of the practical benefits of using these dimensional measures is that they allow for more statistically powerful tests of the potentially distinct implications of these different attachment strategies during adulthood under some circumstances (see Fraley & Spieker, 2003, for simulation results). There is a growing corpus of research demonstrating that the empirically derived dimensional indices of adults’ dismissing and preoccupied states of mind are uniquely associated with different interpersonal behaviors (Fortuna, Roisman, Haydon, Groh, & Holland, 2011; Haltigan, Leerkes, Supple, et al, 2014; Haydon, Roisman, & Burt, 2012; Whipple et al, 2011), social–cognitive processes (Dykas, Woodhouse, Jones, & Cassidy, 2014; Haydon, Roisman, Marks, & Fraley, 2011), and problematic behaviors (Haydon et al, 2012; Martin et al, 2017 [this issue]).…”
Section: Discussionmentioning
confidence: 99%